Materials science and engineering : concepts, methodologies, tools, and applications / Information Resources Management Association, editor. (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, [2017], 2017)
PDFs (1,804 pages) : illustrations.